Pembiasaan Diri Warga Sekolah Melalui Program Adiwiyata Sebagai Upaya Mewujudkan Kecakapan Sosial - Rosyidi, Ahmad Zain; Maryani, Enok; Logayah, Dina Siti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
This research aims to trace and identify the entire series of self-habitualization activities wrapped in the Adiwiyata program at SMP Negeri 30 Jakarta. Each series of the Adiwiyata program at SMP Negeri 30 Jakarta studied has its own purpose and meaning of self-habitualization to strengthen the life skills of the school community implementing the Adiwiyata program. The research approach used in this study is qualitative with a phenomenological model. Data collection for this research was conducted through interviews, observations, and documentation studies. The results of the research on self-discipline practices in the implementation of the Adiwiyata program conducted by the residents of SMP Negeri 30 in Koja District, North Jakarta City, show that the school community had already been practicing self-discipline in preserving the school environment long before applying to become a candidate for the city-level Adiwiyata school. However, at the time SMP Negeri 30 Jakarta applied to become a candidate for the city-level Adiwiyata school. then there is a wider variety of activities within the adiwiyata program, and gradually, self-habits are formed as the residents of SMP Negeri 30 North Jakarta carry out the entire series of adiwiyata program activities within their school environment. One of its main objectives is to utilize the considerable human resources within the school environment to create a clean, safe, comfortable, and enjoyable school during the learning activities at SMP Negeri 30 North Jakarta, as well as to strengthen environmental care activities into social skills.